Which host country government actors are most involved in disputes with foreign investors? - Jeremy Caddel; Nathan M. Jensen (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
Using data on international investment arbitration, the authors catalog the types of state actors involved in disputes and the actions that lead to arbitration. We find that the majority of disputes are the result of actions taken by the executive branch.
Keywords: 330